Pembuatan dan Karakterisasi Selulosa Dari Limbah Kulit Buah Nanas (Ananas Comosus L.) Sebagai Adsorben Zat Warna Remazol Yellow - Lestari, Intan; Permana, Edwin; Hidayat, Dara Shalsa Billah (Jambura Journal of Chemistry, 2025)
Remazol Yellow is a dye that contains an basic amino group and a benzene core, so it is difficult to be naturally degraded by microorganisms and causes environmental pollution. One solution to reduce the dye waste polluted in waters can be done by adsorption method using pineapple peel cellulose as adsorbent. Before turning into pineapple peel cellulose, the NaOH delignification process and H2SO4 hydrolysis were carried out first. The adsorption process for rhodamine B dye was carried out on 2 parameters, namely pH, contact time and determination of the adsorption system using the Langmuir and Freundlich equations at various concentrations of 5, 10, 15, 20, 25, 50, 75 and 100 ppm. Testing the effect of pH on the adsorption of Remazol Yellow was carried out with variations in pH namely 2, 3, 4, 5, 6, 7 and 8. . The results showed the optimum conditions at pH 2, contact time of 30 minutes and the Langmuir isotherm adsorption system with an adsorption capacity of 19.888 mg/g